2017
DOI: 10.1016/j.bbamcr.2017.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of neuronal activity in the Drosophila mushroom body by DopEcR, a unique dual receptor for ecdysone and dopamine

Abstract: G-protein-coupled receptors (GPCRs) for steroid hormones mediate unconventional steroid signaling and play a significant role in the rapid actions of steroids in a variety of biological processes, including those in the nervous system. However, the effects of these GPCRs on overall neuronal activity remain largely elusive. Drosophila DopEcR is a GPCR that responds to both ecdysone (the major steroid hormone in insects) and dopamine, regulating multiple second messenger systems. Recent studies have revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 73 publications
0
22
0
Order By: Relevance
“…Similar compartmental localization was observed at the base of many axon tracts, suggesting AIS localization of DopEcR::Venus in other cell types (data not shown). Because action potentials are generated in the AIS, DopEcR might control signal propagation in response to dopamine and/ or ecdysteroids by modulating spike initiation (Lark et al, 2017). Taken together, our results demonstrate that localization of dopamine receptors divide the cell membrane into spatially distinct compartments, which might allow single neurons respond differently depending on the site of dopamine input.…”
mentioning
confidence: 71%
“…Similar compartmental localization was observed at the base of many axon tracts, suggesting AIS localization of DopEcR::Venus in other cell types (data not shown). Because action potentials are generated in the AIS, DopEcR might control signal propagation in response to dopamine and/ or ecdysteroids by modulating spike initiation (Lark et al, 2017). Taken together, our results demonstrate that localization of dopamine receptors divide the cell membrane into spatially distinct compartments, which might allow single neurons respond differently depending on the site of dopamine input.…”
mentioning
confidence: 71%
“…The application of ecdysone increases nicotine‐induced Ca 2+ in the calyx and cell body region of the MB, whereas the application of DA increases Ca 2+ influx in response to sugar in gustatory receptor neurons. In both cases, the increase in Ca 2+ influx was dependent on DopEcR …”
Section: Dopaminergic Signalling Across Speciesmentioning
confidence: 90%
“…The insect mushroom-bodies (MBs) are not only known as a center for olfactory learning and memory (Dolan et al, 2018;Felsenberg et al, 2018;König et al, 2019;Lyutova et al, 2019;Thum and Gerber, 2019;Turrel et al, 2018;e.g., Warth Pérez Arias et al, 2020;Widmer et al, 2018), they are also involved in the temporal and spatial control of locomotor activity (Besson and Martin, 2005;Helfrich-Förster et al, 2002;Lark et al, 2017;Lebreton and Martin, 2009;Mabuchi et al, 2016;Manjila et al, 2019;e.g., Martin et al, 1998;Serway et al, 2009;Sun et al, 2018;Xiong et al, 2010). In addition, (Castells-Nobau et al, 2019) (Fig.…”
Section: Foxp-ib Expression In the Drosophila Brainmentioning
confidence: 99%
“…The only case where only one set of parameters was affected were the FoxP 3955 mutant flies (Fig. 6) MBs have been shown to affect both spatial and temporal aspects of locomotion (Besson and Martin, 2005;Helfrich-Förster et al, 2002;Lark et al, 2017;Lebreton and Martin, 2009;Mabuchi et al, 2016;Manjila et al, 2019; e.g., Martin et al, 1998;Serway et al, 2009;Sun et al, 2018;Xiong et al, 2010) (Linneweber et al, 2020), but removing FoxP from DCNs showed no effect (Fig. 9B), despite abundant FoxP expression in DCNs (Fig.…”
Section: Foxp Expressionmentioning
confidence: 99%